Masculinity in lesbian "pulp" fiction - Thompson, Paul, 1950- author.
1 online resource.
Keywords: "This book looks specifically and in depth, for the first time, at masculinity in cheap, lesbian-themed paperbacks of the two decades after WW2. It challenges established critical assumptions about the readership, and sets the masculinity imagined in these novels against the "masculinity crisis" of the era in which they were written. The key issue of these novels is couplehood as much as sexuality, and the instability of masculinity leads to the instability of the couple. Thompson coins the term "heteroemulative" to describe the struggle that both heterosexual and homosexual couples have in conforming to heteronormativity. As several of these novels have been republished and remain in print, they have taken on a new relevance to issues of sexuality and gender in the twenty-first century, and this study will attract readers within that area of interest. A valuable read for sociologists studying gender roles, and social historians of the cold war period in the United States. It is suitable for readers of all academic levels, from undergraduate, through postgraduate, to scholars and researchers, but also for a general readership"--